2012
DOI: 10.1590/s1516-31802012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between balance and the level of functional independence among elderly people

Abstract: CONTEXT AND OBJECTIVE: As the overall number of elderly people increases there is a corresponding rise in the number of older persons with disabilities. In order to examine whether there is any relationship between balance and activities of daily living, we evaluated balance and daily activities among elderly people living in the community. DESIGN AND SETTING: Cross-sectional study at Universidade Estadual Paulista (Unesp), Marília, São Paulo, Brazil. METHODS:The study included 70 community-dwelling elderly pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
2
24
1
4
Order By: Relevance
“…These in turn become important factors in the decline of the quality of life of senile elderly persons, as they reduce the degree of functionality and functional independence. 10 The hypothesis of the present study, therefore, was that older elderly persons are more at risk of suffering falls and becoming more functionally dependent, as well as being susceptible to the interference of other variables such as age, cognitive status and medications on postural balance and functional dependence.…”
Section: Introductionmentioning
confidence: 90%
“…These in turn become important factors in the decline of the quality of life of senile elderly persons, as they reduce the degree of functionality and functional independence. 10 The hypothesis of the present study, therefore, was that older elderly persons are more at risk of suffering falls and becoming more functionally dependent, as well as being susceptible to the interference of other variables such as age, cognitive status and medications on postural balance and functional dependence.…”
Section: Introductionmentioning
confidence: 90%
“…Complete dependence on the help of others is the cause of emotional suffering and feelings of helplessness. According to Prat and Scheicher [55], the loss of functional independence is one of the main problems of older people, while independence increases their satisfaction and improves their quality of life. Weeks et al [56] stated that preventing the expansion of functional limitations is a key factor motivating older people to participate in physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Weeks et al [11] reported that preventing further health decline is a key motivator for physical activity participation for older adults. As Prata and Scheicher [30] indicate, loss of independence is one of older adults' major concerns. Experiencing control over life can increase life satisfaction [31] and quality of life [32].…”
Section: Discussionmentioning
confidence: 99%